Analyzing the impact of disaster-related factors on student preparedness using Structural Equation Modelling - Putri, Arinda Soraya; Martin, Adryan Rizky; Setiawan, Eko; Fahmi, Afiqoh Akmalia; Nugroho, Munajat Tri; Putri, Evitania Salmadita; Pratama, Yuda Aditiya (OPSI, 2025)
This study aims to analyse the relationship of disaster factors to the level of preparedness of students in Central Java in facing disasters. This research uses quantitative methods, because data collection in research is related to numbers and uses statistical analysis. The quantitative approach in this study uses the Structural Equation Modelling (SEM) method. Sampling was carried out by purposive sampling method or an assessment that was taken if it met certain criteria in accordance with the research topic, the sample used was 361 respondents. The method used in this research is SEM analysis, which is a multivariate statistical technique that analyses the relationship between variables. Independent variables include knowledge, attitude, policy, environment, training and religiosity. The dependent variable is preparedness. The results of research from independent variables that have an effect and have a positive direction are the attitude variable with a T-statistic value of 7,357, the training variable with a T-statistic value of 4,839 and the religiosity variable with a T-statistic value of 2,352. Variables that have a positive direction, but no effect are the knowledge variable and the policy variable.